In-Training Advising Sessions for New Peer Advisors: Impacts and Benefits - Stephanie Lea Howard (Studies in Self-Access Learning Journal, 2019)
This paper will describe the impact a series of advising sessions had on two university students being trained as peer advisors during the first half of a peer advising training course conducted at a self-access center in the Republic of Turkey. The author provides the rationale for developing the peer tutoring program, the selection procedure, and aspects of the training course. The paper will then focus on the learner development that occurred as a result of the trainees experiencing three advising sessions. The paper explores key training experiences, including insights and observations made by the trainer and trainees to illustrate how the development of the peer advisors was affected.